Isolation of mixed subtypes of influenza A virus from a bald eagle (Haliaeetus leucocephalus) - Redig Patrick T; Ramakrishnan Muthanan A; Chander Yogesh; Jindal Naresh; Goyal Sagar M; Sreevatsan Srinand (Virology Journal, 2010)
Abstract From April 2007 to March 2008, cloacal swabs were obtained from 246 casualty raptors recovered by various wildlife rehabilitation centers in the United States. The swabs were placed in a virus transport medium and transported to the laboratory on ice packs. At the laboratory, the samples were pooled with each pool consisting of five samples. All pools (n = 50) were screened for the presence of avian influenza virus (AIV) using a real time reverse transcription-polymerase chain reaction (rRT-PCR); one of the pools was found positive. All five samples in this pool were tested individually by rRT-PCR; one sample from a bald eagle was found positive. This sample was inoculated in embryonated chicken eggs for virus isolation and a hemagglutinating virus was isolated. Complete genome sequencing of the isolate revealed a mixed infection with H1N1 and H2N1 subtypes. Further analysis revealed that the PB1-F2 gene sequence of H1N1 virus had the N66S virulence-associated substitution. Further studies on ecology and epidemiology of AIV in raptors are needed to help understand their role in the maintenance and evolution of AIV.